Prevention and Treatment of Respiratory Associated Pneumonia in a Patient with Prolonged Artificial Lung Ventilation - Komiljonovich, Ibragimov Nemat; Kalbayevich, Yusupbayev Timur; ogli, Qaxxorov Nodirjon Adxamjon; Shavkatovich, Rixsiboyev Avaz; ogli, Abdumutalov Samandar Ruziqul (Central Asian Journal of Medical and Natural Science, 2022)
This article provides information about treatment of pneumonia. While critically ill patients experience a life-threatening illnes, they commonly contract ventilator-associated pneumonia. This nosocomial infection increases morbidity and likely morbidity as well as the cost of health care. This article reviews the literature with regard to diagnosis, treatment, and prevention. It provides conclusions that can be implemented in practice as well as an algorithm for the bedside clinician and also focuses on the controversies with regard to diagnostic tools and approaches, also treatments.